Tropical Peat Swamp Forest Ecosystem and Floristic Diversity in Pahang, Malaysia - Jusoff, Kamaruzaman; Hassan, Che Hashim; Hamzah, Khali Aziz (2007)
Peat swamp forests are highly significant globally, both for their diverse and threatened species and as representative unique ecosystems. Apart from its critical role in providing habitat for wildlife, the tropical peat swamp forest also acts as a gene bank that harbours potentially useful varieties of plant species. Malaysia’s peat swamp forests also provide crucial benefits and services for the sustainable development of human communities. The objective of the study is therefore to assess the status of the remaining peat swamp forest ecosystem and floristic biodiverstity in Pahang towards the efforts in establishing guidelines for its sustainable management and conservation. This collaborative study was undertaken by the Pahang Forestry Department, United Nation Development Programme/Global Environment Facility (UNDP/GEF)DANIDA focusing on the South East Pahang Peat Swamp Forest (SEPPSF), Pahang, Malaysia. The UNDP/GEF component emphasized on the ecosystem and floristic diversity of the peat swamp forest. The final output from the collaborative efforts was used by the state authority, in particular the Pahang Forestry Department as a guide to manage the remaining peat swamp forest in the state for both ecosystem and floristic diversity conservation and sustainable use of the forest resources. Results indicated that the SEPPSF is very rich in ecosystem and floristic diversity and an integrated management plan is proposed to ensure biodiversity conservation of Peat Swamp Forest in Pahang.